Learning and assessment strategies to develop specific and transversal competencies for a humanized medical education - Tutor, Antonio S.; Escudero, Esther; Nogal Ávila, María del; Aranda, Juan Francisco; Torres, Hortensia; Yague, Josué G.; Borrego, María José; Muñoz, Úrsula; Sádaba, María C.; Sánchez-Vera, Isabel (Frontiers in Physiology, 2023)
Introduction: Medical education should promote the development of skills and abilities that can be applied to real-world work performance. The aim of this study is to evaluate technical and methodological knowledge, as well as physician-patient communication skills, as one of the most important transversal competencies that a good physician should acquire; all this in a reliable, accurate and objective way. Methods: We present a rubric specifically designed and implemented for the evaluation of specific and transversal competencies in the physiology practical sessions, during the second year of the medical degree. The assessment consists in two evaluation tests: 1) a theoretical test that consists of multiple-choice questions. Students must demonstrate that they have acquired adequate theoretical knowledge (specific competency "to know"); 2) a practical test, in which students are evaluated by the rubric through the simulation of a medical consultation. Thus, demonstrating their ability to execute/apply what they have learned in class (specific competency "to know how to do"). They are also evaluated on the transversal competencies that we call "communication with the patient" (transversal competency "to know how to be there") and "dealing with the patient" (transversal competency "to know how to be"). Results: We evaluated whether there were differences in the grades obtained by students when the transversal competencies were not assessed (academic years 2017-2018 and 2018-2019; n=289), and when the transversal competencies were assessed by applying the rubric in the academic years 2019-2020, 2021-2022, and 2022-2023 since the academic year 2019-2020 (n=526). Furthermore, we present a student perception that supports the use of clinical simulation and our rubric as a good method within the competency learning process. Discussion: The acquisition of these competencies, starting from the first courses of undergraduate education, helps to raise the students' awareness in the development of a more humanized medicine, allowing a better response to the patients' needs. Our rubric, which clearly indicate the performance criteria, have become an excellent method to carry out the assessment of competencies, both for students and teachers, since they allow to obtain clear evidence of the level of acquisition and application of knowledge.